Genome-wide studies reveal novel and distinct biological pathways regulated by SIN3 isoforms. - Saha, N.; Liu, M.; Gajan, A.; Pile, L.A. (BMC Genomics, 2016)
The multisubunit SIN3 complex is a global transcriptional regulator. In Drosophila, a single Sin3A gene encodes different isoforms of SIN3, of which SIN3 187 and SIN3 220 are the major isoforms. Previous studies have demonstrated functional non-redundancy of SIN3 isoforms. The role of SIN3 isoforms in regulating distinct biological processes, however, is not well characterized. We established a Drosophila S2 cell culture model system in which cells predominantly express either SIN3 187 or SIN3 220. To identify genomic targets of SIN3 isoforms, we performed chromatin immunoprecipitation followed by deep sequencing. Our data demonstrate that upon overexpression of SIN3 187, the level of SIN3 220 decreased and the large majority of genomic sites bound by SIN3 220 were instead bound by SIN3 187. We used RNA-seq to identify genes regulated by the expression of one isoform or the other. In S2 cells, which predominantly express SIN3 220, we found that SIN3 220 directly regulates genes involved in metabolism and cell proliferation. We also determined that SIN3 187 regulates a unique set of genes and likely modulates expression of many genes also regulated by SIN3 220. Interestingly, biological pathways enriched for genes specifically regulated by SIN3 187 strongly suggest that this isoform plays an important role during the transition from the embryonic to the larval stage of development. These data establish the role of SIN3 isoforms in regulating distinct biological processes. This study substantially contributes to our understanding of the complexity of gene regulation by SIN3.